Le pinete demaniali costiere di Ravenna e Ferrara: analisi dei tipi forestali e strutturali per la scelta del trattamento selvicolturale nel processo di pianificazione - Paolo Cantiani; Fabrizio Ferretti; Giuseppe Pignatti; Giampiero Andreatta; Giovanni Nobili (Annals of Silvicultural Research, 2009)
The state-owned pine forests on the coast of Ravenna and Ferrara: analysis of forest and structure types for choice of silvicultural system in the planning process. Results of the analysis on typology and structure of state forests dominated by maritime pine (Pinus pinaster Ait.) are reported. These formations grow on a narrow coastal belt between Cervia (Ravenna) and Volano (Ferrara), in the Emilia-Romagna region (Italy). The aim of the study is to support the proper silvicultural system in order to satisfy multiple use of pine forests using the analysis of forest types and model types of structure. Main ecological and structural features of principal pine forest types and experimental criteria on silvicultural systems are explained.